Gender and modernity revisited: Dialogues with Joel Kahn. (September 2019) - Stivens, Maila
This article revisits theorising about the relationships between concepts of gender and modernity, drawing on long-term anthropological research on Southeast Asia. From the 1990s on, now well-known feminist critiques pointed to the profound androcentrism of much theorising about modernity, the many lacunae in such work, and the ways in which masculinity has operated as a core constitutive category of the social. Most theorising about modernity, feminists argued, was gendered both by the exclusion of women and a neglect of gender in explorations of the modern. In their turn, feminists have argued strongly for the centrality of genders and sexualities in the making of modern social and cultural forms and pointed to the crucial place of gendered imaginaries within modern social orders, with women being frequently identified and deployed as bearers of nation, 'tradition', and 'civilisation'. Unpacking and challenging the received categories and paradigms – not least 'woman' – has proved demanding, however. Problems have been intensified by prevailing Eurocentrisms, and conceptual divisions of the world into essentialised binaries like 'modern' and 'traditional', 'West' and the 'Rest', and latterly Islam and the West. With increased contests around the concept of modernity – feminist and non-feminist – some writers have argued for a pluralisation of modernity, with such concepts as multiple modernities or alternative modernities, or through conceiving of a global modernity. Engaging critically with such ideas, and grounding the discussion in empirical work on Malaysia carried out in dialogue with Joel Kahn, this article looks to possible further developments in framing debates about gender and the modern, exploring the contributions that locally based, anthropological scholarship can make to theorisations of modernity and its relationship(s) with gender.